A STUDY ON THE GROCERY SHOPPING FACTORS INFLUENCING ON DEMOGRAPHIC CHARACTERISTICS IN HYDERABAD CITY, TELANGANA STATE - M.Shankaraiah; Prof.V. Shekhar (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The grocery market in India will increase 8.02% by 2025 as per the techno. With the competence of in the market fragmentation the grocery market entertained by online markets. The growing the urbanisation and rising the personal products the using of the flexible payment and delivery modes and changeling life the consumer behaviour will hang e by day to day. The study undertaken to know the consumer behaviour of grocery products in organised retail stores.